Technology integration in teaching music in Nigerian higher institutions of learning (2008)
Background: Information and Communication Technologies (ICTs) are generally becoming prevalent in Nigerian higher institutions. Although studies have shown that utilization of ICTs has great potential of ensuring effective delivery in teaching music as well as serve as valuable complimentary resource materials in musical arts educational endeavours, not much is however known about how Nigerian musical arts educators use ICT especially the music related softwares and the individual-level factors that affect ICT use, a gap in blow ledge this study attempted to fill. Materials and Method: A questionnaire was administered to thirty-eight musical arts educators proportionally selected from ten higher institutions in Nigeria offering music with the aim of finding out levels of information technology adoption and utilization, characteristics of ICT use by lecturers, and factors which influence ICT use. Findings: The results show that ICT is used by 94.7% of respondents in the survey. Regular use of ICT was independent of gender and academic rank but varied by institutions. Constraints faced by the music educators include lack of adequate organizational facilitation and lack of skill necessary to use ICT effectively. Other hindrances to ICT use are financial and epileptic electric power supply as well as volume of academics’ workload. Even though use of computers appears high, the potentials of ICTs for facilitating and enhancing music education in Nigeria are still not being fully explored. Conclusions: There is need for formulating educational policies and designing appropriate training and mentoring programs, as well as providing infrastructural support, to help musical arts educators explore the potentials of ICTs to facilitate their job functions.